Desenvolvimento de micropartículas de xilana utilizando reticulante não tóxico visando a liberação cólon-específica - Costa, Silvana Cartaxo da (2014)
The development of a colon-specific delivery system using polymeric microparticles has received great attention in the pharmaceutical field. An interesting group of polymers with potential properties in this area are the hemicellulose. Xylan is a hemicellulose that has the ability to pass through the digestive tract unchanged and its complex structure requires enzymes that are produced specifically by the human colonic microflora, which makes it an interesting raw material in the production of target drug delivery systems. The microparticulate systems can be developed by various techniques. The interfacial crosslinking polymerization is one of the major techniques to produce polysaccharide based microparticles. However, the use of highly toxic crosslinkers often makes the use of this technique limited. The sodium trimetaphosphate (TSTP), a low toxic crosslinking agent, has no adverse effects reported on human beings. The aim of this study was to develop xylan microparticles using sodium trimetaphosphate. The microparticles were characterized by optical microscopy, SEM, XRD and FT -IR. The influence of different parameters on the diameter of the microparticles was analyzed during their development. Toxicity studies against Artemia saline Leach were made to compare the microparticles produced with terephthaloyl chloride and sodium trimetaphosphate. Xylan microparticles showed to be spherical shape, well individualized and with a smooth surface. All different parameters influenced the in size of the microparticles. The FT-IR spectrum of microparticles was similar to xylan, but with the presence of the peak at 1258 cm -1 , which is typical of phosphate ester bonds, that can be attributed to the bond between TSTP and xylan during the crosslinking process. The xylan microparticles produced in this work showed no toxicity at the concentration studied. It be concluded that TSTP was able to produce xylan microparticles with well defined physicochemical characteristics and low toxicity.